A Duoethnographic Exploration of Two Counselor Educators’ Growth in Assessment in Teaching - Phillip L. Waalkes Dr.; Daniel A. DeCino Dr. (Teaching and Supervision in Counseling, 2020)
Assessment in teaching is a challenge for many beginning counselor educators. Although many researchers have discussed the importance of student learning outcomes, few have explored counselor educators’ experiences using assessment in their courses. In this duoethnographic inquiry, we engaged in a critical and reflective dialogue of our experiences with assessment. We aimed to acknowledge our biases, identities, and emotions related to assessment in transformative ways. For [researcher 1], our dialogue helped me gain theoretical and emotional perspective on assessment and inspired specific changes to my assessment practices including focusing more on process-based, low stakes assessment, developing clearer learning goals, and providing feedback from a phenomenological perspective. For [researcher 2], our dialogue helped me link past experiences of being graded to my relationships with teachers, explore my role in subjectivity and performance based assessments, and deconstruct memorable moments of assessment to further my identity development as a counselor educator.
Keywords: pedagogy; grading; student learning outcomes; assessment; counselor education